Understanding the Shari'ah and its place in the Muslim communities of Southeast Asian countries: a Muslim-Malaysian perspective - Hassan, Mohd. Kamal (2015)
As an increasingly strategic geo-political and geo-economic region consisting of the states of Brunei Darussalam, Kampuchea, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Vietnam and Timor-Leste, Southeast Asia has assumed greater international economic, political and religious profile on a global scale. Joined together by ASEAN the above ten countries (excluding Timor-Leste) are committed to actualize the creation of the ASEAN COMMUNITY by the end of 2015, and to work together in facing the threat of religious extremism and militancy. The rise of the Pacific Rim as the new growth center of the world, with China and U.S.A. playing an active economic, military and political roles in the region, the ASEAN COMMUNITY is bound to assume greater significance in the balance of power strategies of the two nations. With approximately 600 million people and the world’s largest Muslim country, Indonesia, Southeast Asia is, moreover, home to roughly 250 million adherents of mainstream Sunni religious tradition in Brunei (population 437,883, 78.8% Muslims), Indonesia (population 253,609, 87.2% Muslims) and Malaysia (population 30,073,353, 61.3% Muslims) as the three Muslim majority countries.